Theory of mind in patients with mild cognitive impairment: A systematic review - Morellini, Lucia; Izzo, Alessia; Ceroni, Martino; Rossi, Stefania; Zerboni, Giorgia; Rege-Colet, Laura; Biglia, Elena; Sacco, Leonardo (Frontiers in Psychology, 2022)
The focus of this systematic review was to collect and align studies which analyze the functionality of theory of mind (TOM) in patients with mild cognitive impairments (MCI). Specifically, we identified 20 papers published between 2012 and 2022 which met inclusion criteria. Papers search, selection, and extraction followed the PRISMA guidelines. In order to summarize data from the papers, we used a narrative synthesis approach. Results in 18 of these 20 papers show that theory of mind (TOM) is impaired in all types of MCI patients—regardless of different etiology and diagnostic criteria. Only 2 out of 20 reported no significant differences in TOM performance between MCI patients and healthy control subjects. The review additionally aimed to bundle the variety of the type of tasks used by the author to assess multiple domains of TOM. This heterogeneity does not allow us to make a comprehensive comparison between the results, so we suggest the need to align the results using the same type of tests and TOM assessment. In the end, our work highlights the 2 neuropsychological studies which confirm more of our results; due to the objective approach adopted to investigate this topic, we suggest exploring this point of view more in future research.